COHESION AND COHERENCE OF ONLINE NEWS CNN INDONESIA DISCOURSE REGARDING THE MURDER CASE OF A FRIED SNACK SELLER IN PARIAMAN, WEST SUMATRA: A DISCOURSE ANALYSIS - Randi, Randi; Sari, Nur Indah (Program Studi Tadris Bahasa Indonesia, 2025)
The ease of accessing information makes it difficult to clarify the truth of the news being reported. One of the right ways to filter information is by conducting cohesion and coherence analysis.This research aims to understand how cohesion and coherence are used in online news regarding the viral case of the fried food vendor murder in Pariaman, West Sumatra, that occurred some time ago. Cohesion and coherence are important criteria and principles in a text. This research is expected to contribute to the development of story writing quality. So that the story can be understood and useful for the readers. Thus, the purpose of writing the story can inspire readers. The method used to analyze cohesion and coherence is descriptive analysis, which is evident in each paragraph. The aspect of cohesion that is analyzed is the aspect of lexical cohesion and grammatical cohesion. The results of this study show that the story